Development of a tourism brand to promote and strengthen the cultural identity of Pile as a tourist destination in Manabí - Andrade Chávez, Mariagracia (2024)
Cultural identity in a commune is crucial to preserve the values that reinforce the sense of belonging and social cohesion. Implementing a tourism brand based on this identity stimulates economic development and raises recognition of the locality. This study aimed to develop a tourism brand proposal that reinforces the cultural identity and promotes the heritage resources of Pile. The methodology was exploratory and descriptive, with both quantitative and qualitative approaches. Surveys were conducted with 160 people, and an exhaustive bibliographic and documentary review was carried out to evaluate the current conditions of the study area. The results showed that, despite a rich cultural heritage, tourism is not a prominent economic activity in the commune, with agriculture being dominant. However, a notable interest in the market for experiences related to local history and traditions was identified. In conclusion, the community’s commitment to improving and consolidating its heritage as a tourist attraction will significantly strengthen its cultural identity.